Pelatihan Digital Enterpreneurship untuk Meningkatkan Kemampuan Berwirausaha Secara Digital Pengusaha UMKM. - Sinta Dameria Simanjunatk (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The COVID-19 pandemic has had a profound impact on all aspects of people's lives. This impact is no exception for small, medium and large entrepreneurs. As a result of the pandemic, the community in general MSMEs must survive and struggle. One thing that MSMEs must do is switch from traditional businesses to digital businesses. To help MSME entrepreneurs switch to digital businesses, digital entrepreneurship training is provided. The training provided starts from Canva's business model, content marketing, website design, Google My Business, social media optimization and power merchants. The method used is lecture and practical training. The results obtained are that MSME entrepreneurs are able to design businesses with the Canva business model, market content, create websites and Google My Business, optimize social media as digital marketing and have an online store.